Development of Flashcard Learning Media Using the Canva Application on Early Reading Material for Grade I Elementary School Students - Dine Trio Ratnasari, Dine trio Ratnasari; Deby Fauzi Assidiqi; Yuyun Yuningsih; Nina Riska (Jurnal Elementaria Edukasia, 2025)
This study was driven by the lack of use of instructional media in classroom learning, particularly in early reading programs in elementary schools. The absence of stimulating learning activities in first grade causes children to be uninterested in reading and view reading as a boring task, both of which exacerbate their reading challenges. Our program was to develop educational resources specifically designed to increase student engagement in the classroom. The resulting instructional media consisted of notecards designed with the Canva application, following the Design and Development research methodology outlined by Richey and Klein. This study used the Planning, Production, and Evaluation (PPE) methodology. Three specialists participated in this study to evaluate the feasibility of the educational media project being developed. This investigation used expert validation questionnaires, work notes, and interviews as instruments. Each expert participated in three iterations of revision and two rounds of validation during the development of the instructional media. Recommendations for improving the standard of the media were proposed. Qualitative data were obtained from quantitative expert assessments using the Likert Scale. Based on expert reviews conducted during the final validation, flashcard learning media were very effective in teaching Indonesian reading skills to early childhood students with an average score of 91.7%.